2017
DOI: 10.1152/ajpheart.00218.2017
|View full text |Cite|
|
Sign up to set email alerts
|

Visualization of three pathways for macromolecule transport across cultured endothelium and their modification by flow

Abstract: Transport of macromolecules across vascular endothelium and its modification by fluid mechanical forces are important for normal tissue function and in the development of atherosclerosis. However, the routes by which macromolecules cross endothelium, the hemodynamic stresses that maintain endothelial physiology or trigger disease, and the dependence of transendothelial transport on hemodynamic stresses are controversial. We visualized pathways for macromolecule transport and determined the effect on these path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
88
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 45 publications
(97 citation statements)
references
References 53 publications
7
88
2
Order By: Relevance
“…Hence there are low magnitude, multidirectional shear stresses at the centre and high magnitude, uniaxial shear stresses at the edge. This behaviour has been captured by polar plots of instantaneous WSS vectors [ 37 , 47 , 48 ], by a combination of the OSI and transWSS metrics, or by a metric termed the Directional OSI [DOSI] [ 37 , 49 ].…”
Section: Characterisation Of Flow In Swirling Wellsmentioning
confidence: 99%
See 3 more Smart Citations
“…Hence there are low magnitude, multidirectional shear stresses at the centre and high magnitude, uniaxial shear stresses at the edge. This behaviour has been captured by polar plots of instantaneous WSS vectors [ 37 , 47 , 48 ], by a combination of the OSI and transWSS metrics, or by a metric termed the Directional OSI [DOSI] [ 37 , 49 ].…”
Section: Characterisation Of Flow In Swirling Wellsmentioning
confidence: 99%
“…That can be achieved by comparing their radial profiles with the radial profile of the cellular property of interest, and/or by changing the physical variables that influence flow patterns. For example, in 12-well plates having a static medium depth of 2 mm, rotated at 150 rpm with an orbital radius of 5 mm, TAWSS decreases from the centre to a radial distance of 7.8 mm before rapidly increasing as it approaches the edge, whereas in the larger 6-well plates with the same medium depth and orbital parameters, TAWSS is uniform until a radial distance of 10 mm before the rapid increase [ 47 , 48 ]. This type of diversity can be used to separate the effects of different metrics.…”
Section: Characterisation Of Flow In Swirling Wellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently developed ''sandwich assays'' employ avidin-and biotin-labeled molecules applied to either side of the tissue to capture the macromolecules as they cross the tight junction barrier. These studies have revealed that barrier function to macromolecules is not uniform across the cell and tissue level and that the leak pathway opens and closes over time (Dubrovskyi et al, 2013;Ghim et al, 2017;Richter et al, 2016).…”
Section: Introductionmentioning
confidence: 99%